Citrus peels in cosmetics (Journal of Face Aesthetics, 2022)
Citrus, in addition to the undoubted taste values appreciated for many centuries, are also characterized by significant health-promoting properties, thanks to the natural ingredients with significant activity. Around the world, the most consumed part of citrus is fresh flesh or the juice squeezed from it. The residue in the form of skins is treated by consumers as waste, but in fact it is a rich source of molasses, pectins and polyphenols, vitamins, mineral salts, essential oils and carotenoids with antioxidant activity. These substances very often appear in cosmetics that are use for face skin care. They can delay the formation of wrinkles and help to maintain skin elasticity.
Keywords: citrus peels; face skin care; orange; lemon; mandarin